1999
DOI: 10.1542/peds.104.1.e1
|View full text |Cite
|
Sign up to set email alerts
|

The Beneficial Effects of Weekly Low-dose Vitamin A Supplementation on Acute Lower Respiratory Infections and Diarrhea in Ecuadorian Children

Abstract: Weekly low-dose (10 000 IU) vitamin A supplementation in a region of subclinical deficiency protected underweight children from ALRI and paradoxically increased ALRI in normal children with body weight over -1 SD. Protection from severe diarrhea was consistent with previous trials. Additional research is warranted to delineate potential beneficial and detrimental interactions between nutritional status and vitamin A supplementation regarding ALRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 21 publications
2
48
0
Order By: Relevance
“…, 54 in their study of the effect of obesity on risk of influenza, pointed to the need to examine the effects of diet and exercise on risk of influenza infection. Previous research, mainly focusing on populations in developing nations, linked malnutrition and micronutrient deficiency with respiratory infection 55 , 56 , 57 , 58 . Several studies also demonstrated benefits of chronic moderate exercise in stimulating immune function and increasing serum concentrations of vitamin D (25 (OH) D) 59 , 60 , 61 .…”
Section: Discussionmentioning
confidence: 99%
“…, 54 in their study of the effect of obesity on risk of influenza, pointed to the need to examine the effects of diet and exercise on risk of influenza infection. Previous research, mainly focusing on populations in developing nations, linked malnutrition and micronutrient deficiency with respiratory infection 55 , 56 , 57 , 58 . Several studies also demonstrated benefits of chronic moderate exercise in stimulating immune function and increasing serum concentrations of vitamin D (25 (OH) D) 59 , 60 , 61 .…”
Section: Discussionmentioning
confidence: 99%
“…17, 34 Individuals with vitamin deficiencies are at increased risk for respiratory infections, 10 and vitamin supplementation has been shown to decrease the rate of respiratory infections in certain populations. [11][12][13][14][15][16][18][19][20] Micronutrients can improve cell-mediated immunity and reduce oxidative stress. 35 Vitamin E supplementation in healthy, well-nourished adults increased delayed hypersensitivity responses, response to hepatitis B vaccine, lymphocyte proliferation, and decreased formation of immunosuppressive prostaglandins.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15][16] Other studies have found no benefit with vitamin supplementation in reducing the rate of respiratory infections. 6, 17-20 Merchant and colleagues demonstrated that vitamin E intake from food sources, but not total intake, was inversely associated with pneumonia risk in US men.…”
Section: Introductionmentioning
confidence: 99%
“…Another study conducted amongst children reported that vitamin A administration was associated with a significant increase in the rate of pneumonia in well-nourished children who received 10,000 IU of vitamin A supplements weekly (20).…”
Section: Effect Of Mdva On Respiratory Infectionmentioning
confidence: 99%